(3GdYdGL HGdaUOs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3bGd bSWG Hf dhbG(B: (3ELgGO GdfaS aj GdhaGA HGdaQGFV GhLH ef LgdgG aj GdfhGad LeYJ ajg eG PcQ LGdjfhS ef GdYdGL HGdaUO s
(3BNQgG (B:s
(3bGd CHhGdaJhM(B: (3EfeG jWHN GdLHf eY GddHf GdMdjH MJi JHOC GdQZhI hgh OSe LOkG jDcd HGdYSd EPG cGf QWHkG , hGdJeQ hGdOHS , hEPG jHS cGf GdLHf aj jHSg EdG Gf WYeg ZjQ WYeg s
(3GfXQgG eY GdeQTO Qbe (B"730"s
(3fSNI ecQQI Yf GdfSNI GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B157 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs